International handbook of research on children's literacy, learning and culture - Hall, Kathy 1952-; Cremin, Teresa; Comber, Barbara; Moll, Luis (Wiley-Blackwell, 2013)
"The International Handbook of Research in Children's Literacy, Learning and Culture presents a careful distillation of the current research in the field of primary years literacy studies"--Publisher.